Tantangan dan Strategi Investasi pada Perusahaan Startup Teknologi di Indonesia - lukman hakim (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The rapid growth of technology Startups in Indonesia is driven by increasing internet penetration and the adoption of digital technologies across sectors. However, these Startups face significant challenges, including market uncertainties, regulatory shifts, and operational issues such as scalability and resource constraints. High-risk yet potentially high-reward investments in this sector demand a nuanced understanding of these challenges and the formulation of effective investment strategies. This study explores the key challenges faced by technology Startups in Indonesia and identifies strategies employed by investors and entrepreneurs to mitigate associated risks. Using a qualitative descriptive approach, this research examines data from industry reports, annual publications, and expert interviews to provide a comprehensive analysis of the ecosystem. Findings highlight that while Startups benefit from Indonesia's large digital market, government support, and international funding, they struggle with regulatory complexities, talent shortages, and fierce competition. Strategies such as diversifying funding sources, leveraging technological innovation, fostering corporate partnerships, and participating in incubation programs are crucial for overcoming these barriers. Insights from this study aim to assist stakeholders in enhancing the sustainability and competitiveness of Indonesia’s Startup ecosystem, ensuring it remains a vital driver of economic growth and innovation in Southeast Asia.